The priciples and practice of management - Brech, E. F. L.; Aldrich, R. M.; Betham, H. E.; Field, A. W.; Lagden, R.G. (London : Longmans, Green and Co. Ltd, 1963)
This volume has gained standing as the authoritative British textbook for the serious study of management - standing thus abroad as well as at home - there is the obligation to bring its content and quality to the higher standards that are required to match the advancing levels of contemporary practice. Such is the purpose of this revised second edition.
Includes bibliographical references and index.
hza 09/08/2018
Loans
Keywords: Management